Mild Copper‐Catalyzed Fluorination of Alkyl Triflates with Potassium Fluoride. (18th May 2014) - Dang, Hester; Mailig, Melrose; Lalic, Gojko
Abstract: A chemoselective catalytic fluorination of alkyl triflates is described using potassium fluoride as a fluoride source. Excellent yields of the desired alkyl fluorides are obtained after one hour at 45 °C using 2 mol % of the copper catalyst. With 10 mol % of the catalyst, full conversion can be achieved in less than 10 minutes at 45 °C, and thus makes this procedure potentially suited for the preparation of 18 F‐labeled PET probes. As a result of the mild reaction conditions, only the substitution products are observed with no evidence of common side reactions, such as elimination. Reported is a preliminary study of the reaction scope, which demonstrates that the fluorination can be performed in the presence of a wide range of functional groups. Evidence suggests an unusual role of the [IPrCuOTf] catalyst as a phase‐transfer catalyst and points to [IPrCuF] as the active fluorinating reagent (IPr=1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene). Abstract : Mit Kaliumfluorid als Fluoridquelle und dem Kupferkatalysator [IPrCuOTf] liefert die Titelreaktion die gewünschten Alkylfluoride in hervorragenden Ausbeuten. Die Methode könnte zur Herstellung von 18 F‐markierten PET‐Sonden geeignet sein. IPr=1, 3‐Bis(2, 6‐diisopropylphenyl)imidazol‐2‐yliden, Tf=Trifluormethansulfonyl.